Multiple sialolithiasis in submandibular gland duct: a rare case report - SILVEIRA JUNIOR,João Batista da (2020)
ABSTRACT Sialolithiasis is a pathological process that affects the major salivary glands. It consists of calcifications that obstruct the parenchyma of the gland and / or the lumen of the ducts. The 37 years old female patient, VBB, leucoderma, attended the stomatology service with a complaint of swelling in the floor of mouth, which she noticed 10 years ago. The clinical and radiographic exams indicated a diagnosis of multiple sialolithiasis in the left submandibular gland duct. Surgical intervention was indicated in this case. Amongst all sialolithiasis cases, 80% affect the submandibular glands. Of these, 70% are isolated sialoliths. Only 5% of cases present more than 3 calcifications. This study aims to report the diagnosis and treatment of a rare case of multiple sialoliths located in the duct of the submandibular gland, which were surgically removed via intraoral access.